Patterns of Tobacco Marketing and User Engagement on Social Media in Indonesia: Challenges for Digital Public Health - Sutrisno, Resti Yulianti; Ekadinata, Nopryan; Sutantri, Sutantri; Binoriang, Dinasti Pudang; Aditjondro, Enrico; Rachfiansyah, Rachfiansyah; Rabindanata, Yosef; Dini, Silvia; Perl, Rebecca; Rachmawati, Riska; Wulandari, Bertha Tesma; Sugiyo, Dianita (UI Scholars Hub, 2026)
Large-scale tobacco marketing on social media has resulted in widespread population-level exposure, particularly in Indonesia, which faces growing challenges in digital public health. This study aimed to assess the associations between platform type and marketing tactics and identify correlations of user engagement. An analytical cross-sectional study was conducted using secondary data from the Tobacco Enforcement and Reporting Movement (TERM), collected from January 2022 to August 2023. A total of 21,255 tobacco marketing posts from social media were analyzed. Platform–tactic associations were examined using Chi-square tests, and multivariable Poisson regression was used to identify factors associated with user engagement. The findings indicated that Instagram (66.8%) and Facebook (24.0%) accounted for the majority of tobacco marketing content. Community-based marketing was the most prevalent tactic (64.7%), followed by direct advertising (20.1%). Bivariate analysis demonstrated a significant association between social media platforms and marketing tactics (p-value <0.001). The Poisson regression model was statistically significant (p-value <0.001). Engagement varied substantially by platform. Compared to YouTube, TikTok demonstrated markedly higher engagement (OR = 35.8), followed by Instagram (OR = 1.88). Corporate social responsibility (OR = 2.39) and community-based marketing (OR = 1.70) were associated with higher engagement. Tobacco promotion on Indonesian social media employs platform-specific strategies to increase exposure and normalize consumption narratives. These patterns underscore substantial digital public health concerns and suggest that enforcement of digital TAPS remains inadequate. Therefore, relevant ministries should strengthen TAPS enforcement and expand targeted digital health education initiatives.